Knowledge and Adoption of Good Management Practices among Litchi farmers in Muzaffarpur District of Bihar - Raj Lakshmi,; Arun Kumar Singh,; Rohit Shelar, (Indian Journal of Extension Education, 2023)
Litchi is one of the nutritionally rich and economically significant fruit of Indian subcontinent. With the advent of Good Management Practices (GMPs), litchi farming technology has advanced drastically. The study was conducted in 2022 in the Muzaffarpur district of Bihar to assess the level of knowledge and adoption of GMPs among litchi farmers and their relationship with the socio-economic profile of litchi growers. The primary data were personally collected through a well-structured interview schedule from 120 respondents. Knowledge and adoption were determined, practicewise on 19 different parameters of GMPs. The highest number of litchi growers (77.50%) had a medium level of knowledge while 71.67 percent had a medium adoption level of the recommended GMPs in litchi production. Variables viz., the area under litchi, cosmopolitness, farming experience, risk preference, innovativeness, and attitude towards GMPs were positively and significantly related to knowledge as well as adoption. Primary work and education were positively and significantly related to adoption. Dissemination of information about modern agricultural practices is necessary for the adoption of GMPs in litchi production